VF-13, a chimeric peptide of VD-hemopressin(α) and neuropeptide VF, produces potent antinociception with reduced cannabinoid-related side effects. (15th September 2020) - Xu, Biao; Xiao, Jian; Xu, Kangtai; Zhang, Qinqin; Chen, Dan; Zhang, Run; Zhang, Mengna; Zhu, Hanwen; Niu, Jiandong; Zheng, Ting; Li, Ning; Zhang, Xiaoyu; et al.
Abstract: Pharmacological evidence indicated a functional interaction between neuropeptide FF (NPFF) and cannabinoid systems, and the cannabinoids combined with the NPFF receptor agonist neuropeptide VF (NPVF) produced antinociception without tolerance. In the present study, VF-13, a chimeric peptide containing the pharmacophores of the endogenous cannabinoid peptide VD-hemopressin(α) (VD-Hpα) and NPVF, was synthesized and pharmacologically evaluated. In vitro, VF-13 significantly upregulated the phosphorylated level of extracellular signal-regulated kinase 1/2 (ERK1/2) in CHO cells stably expressing CB1 receptors and inhibited forskolin-induced cAMP accumulation in HEK293 cells stably expressing NPFF1 or NPFF2 receptors. Moreover, VF-13 induced neurite outgrowth in Neuro 2A cells via CB1 and NPFF receptors. These results suggest that VF-13 exhibits multifunctional agonism at CB1, NPFF1 and NPFF2 receptors in vitro. Interestingly, intracerebroventricular VF-13 produced dose-dependent antinociception in mouse models of tail-flick and carrageenan-induced inflammatory pain via the TRPV1 receptor. In contrast, the reference compound (m)VD-Hpα-NH2 induced CB1 receptor-mediated supraspinal antinociception. Additionally, subcutaneous injection of (m)VD-Hpα-NH2 and VF-13 produced significant antinociception in carrageenan-induced inflammatory pain model. In the tetrad assay, our data demonstrated that VF-13 elicited hypothermia, but not catalepsy and hypoactivity after intracerebroventricular injection. Notably, VF-13 produced non-tolerance forming antinociception over 6 days treatment in both acute and inflammatory pain models. Furthermore, VF-13 had no apparent effects on gastrointestinal transit, pentobarbitone-induced sedation, food intake, and motor coordination at the supraspinal level. In summary, VF-13, a novel chimeric peptide of VD-Hpα and NPVF, produced non-tolerance forming antinociception in preclinical pain models with reduced cannabinoid-related side effects. Highlights: VF-13 is a novel multifunctional agonist for both CB1 and NPFF receptors in vitro VF-13 exerts central and peripheral analgesia in a mouse model of inflammatory pain. Intracerebroventricular VF-13 shows potent analgesia in the mouse tail-flick test. VF-13 produces TRPV1 receptor-mediated supraspinal analgesia without tolerance. VF-13 shows minimized catalepsy, hypoactivity, constipation, and sedative activity.